Incorporating Physical Co-presence at Events into Digital Social Networking - Counts, Scott; John, Geraci (Association for Computing Machinery, Inc., 2006)
As mobile devices become location-aware, it will become possible to know when people are physically co-located and to incorporate this information into social software. Is this valuable? A prototype social networking system based on physical co-presence was created and tested wizard-of-oz-style at four different physical social events by providing event attendees a digital link back to others at the event. Usage of the system was higher than expected, suggesting a meaningful role for incorporating shared physical events into social networking software. Usage and questionnaire analyses suggest some guidelines for design of such systems.